ILMU PENGETAHUAN DAN TEKNOLOGI DALAM HISTORIS PERADABAN MANUSIA: TINJAUAN INKUIRI FILOSOFIS - Harry Yulianto; Iryani Iryani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Science and technology were very helpful in activities to meet the needs of human life. This paper aims to discuss the role of science and technology in the history of human civilization, starting from history, philosophy, and the use of science and technology in everyday life. The method of writing this article uses a philosophical inquiry method, which involves the use of intellectual analysis mechanisms to clarify meaning, make values real, identify ethics, and study the nature of knowledge. The results indicates that the course of human history proves that the progress of human civilization was triggered by the development of science and technology. With the use of science and technology, humans can carry out all their activities easily and efficiently. Science and technology were born and present in the midst of humans to provide enlightenment.